Self-management interventions for gestational diabetes in Africa: a scoping review - Andrews Adjei Druye; Gifty Owusu; Naomi Kyeremaa Yeboa; Christian Makafui Boso; Gifty Osei Berchie; Bernard Nabe; Susanna Aba Abraham; Frederick Nsatimba; Dorcas Frempomaa Agyare; Joyce Agyeiwaa; Rita Opoku-Danso; Christiana Okantey; et al. (BMC, 2024)
Abstract Background Gestational diabetes (GD) can threaten the health of both the mother and the foetus if it is not effectively managed. While there exists a growing body of research on self-management interventions for GD, there is a lack of reviewed studies regarding the various self-management interventions in Africa. The purpose of this review is to map the evidence of self-management interventions for GD in Africa. Methods Searches for records were conducted in four major databases, including PubMed, PubMed Central, Science Direct and Journal Storage. Additional documents from Google and Google Scholar were also added. The guidelines for conducting scoping reviews by Arksey and O'Malley were followed. Results The results revealed that intermittent fasting, education on diet, insulin injection, blood glucose monitoring, physical activities, lifestyle modification and foot care were the available self-management interventions for GD in Africa. Most of the reviewed studies reported intermittent fasting and patient education as effective self-management interventions for GD in Africa. The barriers identified in the reviewed studies were either patient-related or facility-related. Patient-related barriers included lack of awareness, and negative attitude, while facility-related barriers included lack of access to education on GD, especially, face-to-face educational interventions. Conclusion It is crucial to consider the cultural and personal needs, as well as the educational level of women with gestational diabetes when creating an effective self-management intervention. Optimal results can be achieved for self-management of gestational diabetes by integrating multidisciplinary approaches.